definition: |
emap :: Show a => (b -> c) -> Graph a b -> Graph a c emap f = gmap (\(p,v,l,s)->(map1 f p,v,l,map1 f s)) where map1 g = map (\(l,v)->(g l,v)) |
demand: |
no demanded arguments |
deterministic: |
deterministic operation |
documentation: |
--- Map a function over the 'Edge' labels in a graph. |
failfree: |
<FAILING> |
indeterministic: |
referentially transparent operation |
infix: |
no fixity defined |
iotype: |
{(_,_) |-> {ufold}} |
name: |
emap |
precedence: |
no precedence defined |
result-values: |
{ufold} |
signature: |
Prelude.Show c => (a -> b) -> Graph c a -> Graph c b |
solution-complete: |
operation might suspend on free variables |
terminating: |
possibly non-terminating |
totally-defined: |
possibly non-reducible on same data term |